2017
DOI: 10.18632/oncotarget.16791
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-gene panel analysis in a case series of 255 women with hereditary breast and ovarian cancer

Abstract: As new genes predisposing to breast (BC) and ovarian cancer (OC) are constantly emerging, the use of panels of genes analyzed by Next-Generation Sequencing (NGS) is increasing in clinical diagnostics. The identification of a large number of new germline mutations allows for deeper knowledge of cancer predisposition, although raising many questions about patient management.BC and OC patients recruited by our counseling service between 2012-2015 were included in this study. DNA was extracted from peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1
11

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 43 publications
7
62
1
11
Order By: Relevance
“…High throughput NGS‐based multiple gene panel analyses are routinely used for genetic risk assessment in HBOC. Several studies have confirmed the suitability of the commercially available TSCP for HBOC diagnostics . In our study, we performed a systematic screen for PVs in 94 cancer predisposing genes via NGS and CGH.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…High throughput NGS‐based multiple gene panel analyses are routinely used for genetic risk assessment in HBOC. Several studies have confirmed the suitability of the commercially available TSCP for HBOC diagnostics . In our study, we performed a systematic screen for PVs in 94 cancer predisposing genes via NGS and CGH.…”
Section: Discussionmentioning
confidence: 70%
“…Twenty‐five PVs were detected by NGS in BRCA1/2 negative, high risk HBOC patients, leading to a detection rate of 10.6% (25/235). This is higher compared to a former study by Tedaldi et al ., 2017, who discovered PVs in 8.6% of 198 patients with the same NGS‐based panel screening . This discrepancy could be explained by our stringent inclusion criteria for patients in our cohort; a heterozygosity risk ≥20%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…While most of the published multigene panel studies tested patients of (mostly) European ancestry, a limited number of studies have analyzed other populations. We therefore compared the frequency of TP53 carriers among cohorts of patients with different ancestries and without previous BRCA1/2 testing (BRCA unknown) for Europeans (Bunnell et al., ; Buys et al., ; Castera et al., ; Couch et al., ; Couch et al., ; Doherty, Bonadies, & Matloff, ; Eliade et al., ; Kapoor et al., ; Kraus et al., ; Moran et al., ; Pinto et al., ; Rummel, Lovejoy, Shriver, & Ellsworth, ; Schroeder et al., ; Shirts et al., ; Susswein et al., ; Tedaldi et al., ; Tung et al., ; Tung et al., ) Asians (Kwong et al., ; Lin et al., ; Ng et al., ; Rajkumar, Meenakumari, Mani, Sridevi, & Sundersingh, ; Wong et al., ; Yang et al., ), and Middle Easterns (Jalkh et al., ; Lolas Hamameh et al., ).…”
Section: Resultsmentioning
confidence: 99%